Analisis Dan Perancangan Sistem Absensi Menggunakan Teknologi Berbasis Web di SMK 11 PGRI - Azuan Syahrir; Heppy Azizzul Khakim; Puniko Dhino Sae; Rafli Azhar Nugraha (Shofanah Media Berkah, 2023)
The attendance system is an important part of managing student attendance at school. In the digital era, using the web can increase the efficiency and accuracy of the attendance process. Therefore, this journal aims to analyze and design a web-based attendance system for SMKN 11 PGRI. The method used includes needs analysis, system design and prototype implementation. The result of this study is an attendance system that increases efficiency and accuracy and makes it easier to track student attendance at SMKN 11 PGRI. This study identified the need for SMK 11 PGRI to build an attendance system through interviews with the school and related users. The design of a web-based attendance system includes a user interface, attendance function, integration with student data, and attendance report design. The implementation of the attendance system prototype using the selected technology gives satisfactory results in terms of efficiency, accuracy and availability of information. The implemented web-based attendance system allows students to take easy-to-use web-based online classes. Student attendance data will be automatically stored in a central database that can be seen by teachers and school staff. Additional functions such as attendance notification, attendance reporting, and real-time attendance monitoring have also been realized. Testing of this attendance system prototype has achieved satisfactory results in terms of efficiency, accuracy and availability of information. The application of this prototype attendance system provides an easier and more integrated solution for the school attendance process. The use of web-based technology also allows easy access and real-time tracking of student attendance. In conclusion, this web-based attendance system is expected to improve student attendance management at SMKN 11 PGRI and become the basis for further development.